2011
DOI: 10.1021/jp2033774
|View full text |Cite
|
Sign up to set email alerts
|

Methane Dissociation on High and Low Indices Rh Surfaces

Abstract: We present DFT calculations of the energetics of the elementary reaction steps in the dehydrogenation of CH 4 to C on extended Rh(111) and Rh(211) surfaces. The results are compared to the energetics for the same reactions on a planar (111) surface and the edge atoms that are shared between two (111) facets of a nanorod model. The adsorption energies between comparable surfaces of the extended and nanorod models are very similar. Only C adsorbs significantly stronger on the planar surface of the nanorod model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
5
27
0
Order By: Relevance
“…The barrier is lower by 0.23 eV when compared to that obtained for the Ni (1 1 1) flat surface. As expected, the presence of step sites has a strong influence on the activation energy [72][73][74][75]. This must be attributed to the strong bonding of CH 3 at the step edge.…”
Section: Methane Dissociation On Ni (5 5 3)supporting
confidence: 57%
“…The barrier is lower by 0.23 eV when compared to that obtained for the Ni (1 1 1) flat surface. As expected, the presence of step sites has a strong influence on the activation energy [72][73][74][75]. This must be attributed to the strong bonding of CH 3 at the step edge.…”
Section: Methane Dissociation On Ni (5 5 3)supporting
confidence: 57%
“…This observation is strikingly different with the process on almost all transition metal surfaces where the CH dissociation is the rate-determining step. [60][61][62][63][64] Based on the calculated results, it can be inferred that CH 2 is a kinetically significant intermediate and is the most abundant species on the IrO 2 (110) surface. Therefore, by controlling the reaction conditions at mild temperature, it could be possible to block CH 4 dehydrogenation after the first two dehydrogenation reactions and achieve selective dehydrogenation to CH 2 .…”
Section: View Article Onlinementioning
confidence: 92%
“…and Blaylock et al[36], while an experimentally reported value of 715 kJ/mol was reported by Isett et al[76] for the same facet. On the other hand for Rh, in the work of Bunnik et al[74] a value of 705 kJ/mol was reported for Rh(111), whereas for the same surface adsorption energies as high as 775, 813 and 825.0 kJ/mol were calculated by Zhang et al[77], van Grootel et al[78] and Wang et al[79] respectively. Based on the overall satisfactory agreement described above, there is confidence that also the values of the calculated activation energies through the UBI-QEP framework lie within physically realistic limits and represent the surface energetics reasonably.There is a trend identified in the estimated chemisorption heats, wherein most of those of CHx * species are larger for Rh in comparison to Ni suggesting a stronger binding for all these intermediates.…”
mentioning
confidence: 89%